Resection of iliac artery to sigmoid colon fistula in patient with prior bowel resection and endovascular aortic repair with hypogastric coiling - Michael Chaney, MD; Nicholas Stevens, DO; Samuel Coster, DO; Matthew Welter, BS; David Minnick, DO; Saad Shebrain, MD (Journal of Vascular Surgery Cases and Innovative Techniques)
Expedient recognition of arterial-enteric fistulas is important in optimizing patient outcomes. The most commonly described aortoenteric fistula is between the abdominal aorta and third portion of the duodenum that overlies it. This has historically been reported as a rare complication of open aortic aneurysm repair but also has been seen in endovascular repairs. Herein described is a case of a 77-year-old male with history of endovascular aortic repair and left hypogastric coiling for aneurysm who presented with a much rarer form of fistula between the residual sigmoid colon, status-post sigmoidectomy for diverticulitis, and the left hypogastric artery.